Susceptibility-weighted Imaging in Neuroradiology: Practical Imaging Principles, Pearls and Pitfalls - Loai Aker (17128867) (2022)
Susceptibility-weighted imaging (SWI) was one of the recent and helpful advancement in magnetic resonance imaging. Its utilization -provided valuable information for the radiologists in multiple fields, including neuroradiology. SWI was able to demonstrate cerebral paramagnetic and diamagnetic substances. Therefore, the applications of this imaging technique were diverse in research and clinical neuroradiology. This article reviewed the basic technical steps, various clinical applications of SWI, and potential limitations. The practicing radiologist needs to be oriented about using SWI and phase images in the right- and left-handed MRI systems to demonstrate different brain pathologies, including neurovascular diseases, traumatic brain injuries, brain tumors, infectious and inflammatory, and neurodegenerative diseases. Other Information Published in: Current Problems in Diagnostic Radiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1067/j.cpradiol.2021.05.001